2019
DOI: 10.1002/wer.1162
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid silica aerogel nanocomposite adsorbents designed for Cd(II) removal from aqueous solution

Abstract: Hybrid silica aerogel (HSA) nanoparticles were synthesized by sol–gel method and drying at ambient pressure. Also, two magnetic nanocomposites of HSA with Fe3O4 nanoparticles and chitosan (CS) were prepared including HSA‐Fe3O4 and HSA‐Fe3O4‐CS. The morphology, structure, and magnetic properties of the HSA as well as its nanocomposites were analyzed by SEM, XRD, TGA, VSM, and ATR‐FTIR techniques. The saturation magnetization (Ms) values for the Fe3O4 NPs, HSA‐Fe3O4, and HSA‐Fe3O4‐CS nanocomposite film were 69.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Cadmium removal was also attempted by Shariatinia and Esmaeilzadeh [ 184 ], using hybrid silica aerogel (HSA) nanoparticles and two magnetic nanocomposites of HSA with Fe 3 O 4 nanoparticles and chitosan. TEOS and APTMS were used as the HSA precursors, and the drying occurred at ambient conditions.…”
Section: Silica Aerogelsmentioning
confidence: 99%
“…Cadmium removal was also attempted by Shariatinia and Esmaeilzadeh [ 184 ], using hybrid silica aerogel (HSA) nanoparticles and two magnetic nanocomposites of HSA with Fe 3 O 4 nanoparticles and chitosan. TEOS and APTMS were used as the HSA precursors, and the drying occurred at ambient conditions.…”
Section: Silica Aerogelsmentioning
confidence: 99%
“…Today, the world is facing a lot of water shortage and pollution. With the advancement of science and technology, demands have increased for dyes and pigmentation; nonetheless, numerous waste dyes used in various industries are entering rivers and seas as wastewaters. A large amount of industrial wastewaters is colored because a variety of industries including cosmetics, food, coloring, and textiles dispose their waste colors into water. Many industrial dyes are not directly toxic, but they produce carcinogenic compounds, such as aromatic amines, during anaerobic degradation. Although most of these materials are naturally decomposed, the importance of using efficient and economical methods to eliminate contaminants is evident. …”
Section: Introductionmentioning
confidence: 99%
“…However, the results in Figure c demonstrated that Na + , K + , Mg 2+ , and Ca 2+ had little effect on Cd 2+ adsorption even at a high concentration. The adsorption capacities of HMMNs and other reported materials are compared and presented in Figure d. As can be seen, the HMMNs displayed higher adsorption capacity.…”
Section: Resultsmentioning
confidence: 99%